Lymphoma of the thyroid gland: a clinicopathologic study over a period of five years in a tertiary care center - Anjit, U.; Gopal, Ajesh (International Journal of Research in Medical Sciences, 2017)
Background: Primary Thyroid Lymphoma (PTL) is uncommon, accounting for only 5% of thyroid neoplasmsand less than 2.5 to 7% of extranodal lymphomas. The study aims to analyze the histopathological findings and to correlate it with clinical features. Methods: This study includes cases of PTL received in the department of pathology in a tertiary care center, Kerala, south India over a period of 5 years. Patient details and follow up data were obtained by communication with treating doctors and reviewing the hospital records. All cases had a minimum follow up of 6 months. Results: 15 cases of PTL were diagnosed over the five year period. In total 72 cases of extranodal lymphomas were diagnosed, thus forming 20.83% of extra nodal lymphomas. Lymphocytic thyroiditis was present in 93.3%. Most of the cases were Extranodal Marginal Zone B Cell Lymphoma (EMZBCL) and Diffuse Large B Cell Lymphoma (DLBCL). Conclusion: It is important to consider the diagnosis of primary thyroid lymphoma in patients presenting with an enlarging neck mass especially with the history of Hashimoto’s thyroiditis. Random microscopic foci of DLBCL or small areas of MZBL could be overlooked examination or missed with limited sampling. The distinction between MZBL and DLBCL in the thyroid is clinically significant.